Tort Liability for Drug Damage A Comparative Study between the Civil Code of the State of New York and the Iraqi Civil Code - Hamad, Osamah; Abdul-Khazali, Haider (Journal of Legal Sciences, 2025)
Relying on criminalization and punishment to combat drug abuse is insufficient. It must take multiple legal dimensions. Civil law must play an effective and influential role alongside the legal system addressing drug-related harms, through tortious liability rules to remedy such harms. This will provide civil deterrence alongside criminal deterrence. Civil law can define the scope of these victims by establishing the legal basis for compensation based on tortious liability rules. Establishing the right to civil compensation for drug victims requires a logical legal basis that facilitates the victim's proof and adjudication before civil courts. Tortious liability can be another legal means of imposing financial penalties to combat this harmful act (illicit drug trafficking) and provide redress for victims harmed by drugs.